How to use the elasticity of a badminton racket to increase its speed by 80%? - Phomsoupha, M.; Laffaye, G.; Cohen, C.; Clanet, C. (Computer Methods in Biomechanics and Biomedical Engineering, 2015)
Volltext auch unter: https://www.researchgate.net/publication/278521302_How_to_use_the_Elasticity_of_a_Badminton_Racket_to_increase_its_Speed_by_80